Evaluation of Estrogen Alpha Receptor (ER-Α) and Progesterone-A Receptor (PR-A) Expression in the Oviducts and Uterus of Indonesian Local Rabbits after Induced by Several Method of Pseudo-Pregnancy - Syafruddin, Syafruddin; Siregar, Tongku Nizwan; Wahyuni, Sri; Gholib, Gholib (Trends in Sciences, 2023)
The objective of this study was to determine the expression of ER-A and PR-A in the oviduct and uterus of pseudo-pregnant rabbits after induced by several induction methods of pseudo-pregnancy. This study used 30 local rabbits, aged 1 - 1.5 years, body weight of 2.8 - 3.0 kg and clinically healthy. Rabbits were divided into 6 groups (n = 5), namely: K1 (negative control, given 1.5 mL physiological NaCl injection), K2 (positive control, given 100 IU eCG injection and mated with male rabbits, followed by 75 IU hCG injection 3 days later), K3 (given 100 IU eCG injection followed by injection of 75 IU hCG 3 days later), K4 (artificial copulation was performed by inserting a 1 cm long cotton bud into the rabbit’s vagina), K5 (ovulation induction by injection of 50 IU hCG) and K6 (ovulation induction by injection of 5 g GnRH). On the 8th day after treatment, rabbits were euthanized and their oviduct and uterus organs were taken for histological preparation and stained using the immunohistochemical staining. The expression of ER-A and PR-A was valued using the intensity score and analyzed using the Kruskal-Wallis test followed the Mann Whitney U test. The expression ER-A in the infundibulum, ampullary and isthmus of K1 was significantly different (p < 0.05) from K2 - K6 rabbits. The ER-A expression in the endometrium of uterine horn of K1 and K3 was significantly different with K2, K4, K5 and K6 rabbits (p < 0.05). Furthermore, PR-A expression in oviducts of K1 and K3 was lower than that in K2, K3, K5 and K6 (p < 0.05) and the expression in the endometrium, uterine glands and myometrium of K2 - K6 was higher than K1 rabbits (p < 0.05). In conclusion, the hormonal induction could be used to induce pseudopregnancy in local rabbits based on the ER-A and PR-A expressions in oviduct and uterus. HIGHLIGHTS Pseudo-pregnant rabbits are needed for research purposes in the field of reproduction Several methods of induction of pseudo-pregnancy in rabbits have been carried out in this study Pseudo-pregnancy induction cause changes in the concentration of reproductive hormones (progesterone and estrogen) These changes can be detected based on the presence of receptors for these two hormones (PRA and ERα) in reproductive tract of four groups of rabbits and the results were then evaluated GRAPHICAL ABSTRACT